2017
DOI: 10.1200/jco.2016.70.8297
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-Trop-2 Antibody Drug Conjugate Sacituzumab Govitecan (IMMU-132) in Heavily Pretreated Patients With Metastatic Triple-Negative Breast Cancer

Abstract: Purpose Trop-2, expressed in most triple-negative breast cancers (TNBCs), may be a potential target for antibody-drug conjugates. Sacituzumab govitecan, an antibody-drug conjugate, targets Trop-2 for the selective delivery of SN-38, the active metabolite of irinotecan. Patients and Methods We evaluated sacituzumab govitecan in a single-arm, multicenter trial in patients with relapsed/refractory metastatic TNBC who received a 10 mg/kg starting dose on days 1 and 8 of 21-day repeated cycles. The primary end poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
203
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(228 citation statements)
references
References 43 publications
8
203
1
Order By: Relevance
“…29 Trop-2 expression in archived tissues was examined in 150 patients; however, because nearly all specimens were positive, it is not possible to conclude that the prescreening of archived tissue would sufficiently enrich patient selection. It is important to note that safety and efficacy assessments were performed in a diverse population of patients with metastatic cancers who had received multiple and varied prior treatment regimens, including about 30% who received a topoisomerase I inhibitor (primarily patients with gastrointestinal and small cell lung cancer who received an irinotecan-containing regimen or topotecan).…”
Section: Safety and Pharmacokinetics Of Immu-132/ocean Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…29 Trop-2 expression in archived tissues was examined in 150 patients; however, because nearly all specimens were positive, it is not possible to conclude that the prescreening of archived tissue would sufficiently enrich patient selection. It is important to note that safety and efficacy assessments were performed in a diverse population of patients with metastatic cancers who had received multiple and varied prior treatment regimens, including about 30% who received a topoisomerase I inhibitor (primarily patients with gastrointestinal and small cell lung cancer who received an irinotecan-containing regimen or topotecan).…”
Section: Safety and Pharmacokinetics Of Immu-132/ocean Et Almentioning
confidence: 99%
“…29,[33][34][35] Sacituzumab govitecan has an excellent PK profile with a low fraction of SN-38G, resulting in lower rates of diarrhea and a manageable toxicity profile. 29,[33][34][35] Sacituzumab govitecan has an excellent PK profile with a low fraction of SN-38G, resulting in lower rates of diarrhea and a manageable toxicity profile.…”
Section: Safety and Pharmacokinetics Of Immu-132/ocean Et Almentioning
confidence: 99%
“…This ADC has the humanized anti‐TROP2 mAb conjugated to a toxic payload, SN‐38 (7‐ethyl‐10‐hydroxycamptothecin, the active metabolite of irinitecan). SN‐38 is a type I topoisomerase inhibitor that causes double‐stranded DNA breaks and apoptosis, which has been reported to be active in patients with advanced, metastatic triple‐negative breast cancer (mTNBC) and metastatic nonsmall‐cell lung cancer (mNSCLC) . In general, ADC treatment has undesired side effects caused by the expression of the target antigen on normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…SN-38 is a type I topoisomerase inhibitor that causes double-stranded DNA breaks and apoptosis, which has been reported to be active in patients with advanced, metastatic triple-negative breast cancer (mTNBC) and metastatic nonsmall-cell lung cancer (mNSCLC). 27,28 In general, ADC treatment has undesired side effects caused by the expression of the target antigen on normal tissue. In those trials, sacituzumab govitecan was well tolerated as well as in animal models, 29 and it was suggested that TROP2 may be poorly accessible in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This novel ADC (also known as IMMU‐132) can bind to LIV‐1 expressing cancer cells and release the cell‐killing agent (monomethyl auristatin E) into target cells upon internalization (Sussman et al, ). A combination of PARP inhibitors (talazoparib or olaparib) and SGN‐LIV1A exhibits strong antitumor effects and also reduces the growth of tumor in mice models of TNBC (with BRCA1/2 mutation; Bardia et al, ; Moscetti et al, ).…”
Section: Antibody Drug Conjugatesmentioning
confidence: 99%